INFLUENCE OF BANK STABILITY ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN SOUTH SUDAN - Chol, Bak Barnaba; Nthambi, Dr. Elizabeth Kalunda; Kamau, Dr. Joseph (American Journal of Finance, 2019)
Purpose: The purpose of the study was to examine the influence of bank stability on the financial performance of commercial banks in South Sudan Methodology: The study was guided by the CAMEL model metrics in measuring stability and its influence on the financial performance of commercial banks measured by ROA and ROE. The study was primarily grounded on the CAMEL model. The study further adopted the positivism philosophy which guided the research. The research employed a descriptive research design. The population for the study was 24 commercial banks in south Sudan from which the research targeted one senior manager. The research relied on a mixed methodology which encompassed both quantitative and qualitative data. Secondary data was collected for the period 2012-2017 from audited annual financial reports of individual banks and from the Central Bank of South Sudan reports while primary data was collected by use of a semi-structured questionnaire. The collected data into SPSS 23 for subsequent descriptive and inferential statistical analysis. Results: The correlation tests indicated a strong positive effect of asset quality on the financial performance of commercial banks ( r=0 .784); a strong positive effect of management efficiency (r= 0.758) and liquidity (r=0 .620). Unique contribution to theory, practice and policy: The study recommends that at the bare minimum the management of commercial banks should benchmark with industry experts on how to enhance their services and product offering to better their asset quality scores. Further the study recommends that banking institutions that have shied away from lending activities should reconsider the potential benefits that may accrue from undertaking lending activities. The study therefore recommends that banks should be encouraged to look beyond local market and strategically expand their operations to other geographical markets and sectors of the economy. Location of bank branches is strategically paramount if banks must maximize return on investment.